2021
DOI: 10.3390/d13080394
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Descriptions of Two New Tardigrade Species along with the New Record of Mesobiotus skorackii Kaczmarek et al., 2018 from Canada

Abstract: Two new tardigrade species from a moss sample collected in Canada, one representing Macrobiotus hufelandi complex and the second one belonging to the genus Bryodelphax, are described. Integrative analysis was undertaken based on morphological and morphometric data (using both light and scanning electron microscopy (SEM)) combined with multilocus molecular analysis (nuclear sequences, i.e., 18S rRNA, 28S rRNA and ITS-2 as well as mitochondrial COI barcode sequences). Based on COI sequences, Macrobiotus birendra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 81 publications
1
5
1
Order By: Relevance
“…Although there are many controlled studies in the developed world, there are no reports of studies with long follow up in resource poor setting. We have published 4 articles with regard to response and resistance in our patients with CML [13][14][15][16]. We hypothesize that the survival in our set up is similar to well controlled studies elsewhere.…”
Section: Introductionsupporting
confidence: 68%
“…Although there are many controlled studies in the developed world, there are no reports of studies with long follow up in resource poor setting. We have published 4 articles with regard to response and resistance in our patients with CML [13][14][15][16]. We hypothesize that the survival in our set up is similar to well controlled studies elsewhere.…”
Section: Introductionsupporting
confidence: 68%
“…-Bry. mareki is a valid species, evidently showing a unique EEs morphology, but the taxon requires a revision of the important character of ventral plate configuration, which in our examination was not in agreement with the original species description (Kayastha et al, 2021).…”
Section: Summary Of Recommendationscontrasting
confidence: 59%
“…We interpreted this as the visible dark/black areas of the cuticular plates visible when specimens are viewed with PhC. When our results showed that these dark areas are present to some degree in all species that we examined, and that these results differed to those of Gąsiorek et al (2020a) and Kayastha et al (2021) who determined that "dark granules" are absent from the dorsal plates of some 'weglarskae group' species, we needed to investigate this character further in order to understand these discrepancies.…”
Section: Cuticular Sculpture and Reliefmentioning
confidence: 72%
See 2 more Smart Citations